2018
DOI: 10.1038/s41598-018-28702-5
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit–hyperactivity disorder is associated with allergic symptoms and low levels of hemoglobin and serotonin

Abstract: This study investigated whether common comorbidities or biochemical factors, such as allergic disease, anemia, inflammation, and neurotransmitters, are singly or additively associated with an increased risk of attention deficit–hyperactivity disorder (ADHD). We recruited 216 children diagnosed with ADHD and 216 age-, sex-, height-, weight-, and class-matched controls from 31 elementary schools in Taipei, Taiwan. The International Study of Asthma and Allergies in Childhood questionnaire was used to measure alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 48 publications
0
42
0
2
Order By: Relevance
“…We also found that the proportion of Enterococcus was significantly increased in the ADHD group, and Enterococcus has been reported to be closely related to neurotransmitter release. One study demonstrated that Enterococcus abundance is significantly increased in mice lacking the 5-HT transporter (Singhal et al, 2019); deficiency of this transporter can lead to decreased 5-HT levels, which is related to ADHD onset (Wang et al, 2018). Interestingly, a study showed Enterococcus could lead to excessive intestinal conversion of levodopa (the first-line treatment for Parkinson's disease) into dopamine, however, peripheral dopamine cannot penetrate the BBB to enter the CNS, thus reducing the effectiveness of levodopa (Maini Rekdal et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the proportion of Enterococcus was significantly increased in the ADHD group, and Enterococcus has been reported to be closely related to neurotransmitter release. One study demonstrated that Enterococcus abundance is significantly increased in mice lacking the 5-HT transporter (Singhal et al, 2019); deficiency of this transporter can lead to decreased 5-HT levels, which is related to ADHD onset (Wang et al, 2018). Interestingly, a study showed Enterococcus could lead to excessive intestinal conversion of levodopa (the first-line treatment for Parkinson's disease) into dopamine, however, peripheral dopamine cannot penetrate the BBB to enter the CNS, thus reducing the effectiveness of levodopa (Maini Rekdal et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, no association of this IL-1RN polymorphism with ADHD was found in a larger sample [41]. Comorbidity with allergic and autoimmune disorders such as atopic eczema, allergic rhinitis and asthma is another factor that could increase the risk for ADHD and future research may lead to a better understanding of the mechanisms underlying the observed comorbidity [38,[42][43][44]. In a meta-analysis and a large-scale genome-wide association study (GWAS), associations between asthma and ADHD were found in both children and adults [45,46].…”
Section: Inflammation and The Relationship With Adhdmentioning
confidence: 96%
“…In a meta-analysis and a large-scale genome-wide association study (GWAS), associations between asthma and ADHD were found in both children and adults [45,46]. Also, patients with ADHD and asthma had similar brain region dysfunctions and higher levels of cytokines and IgE compared to healthy children, resulting in alterations to the regions in the brain associated with emotional and behavioural control [38,42,47]. The involvement of autoantibodies in ADHD has been suggested but this is an unknown causal association [33,48].…”
Section: Inflammation and The Relationship With Adhdmentioning
confidence: 99%
“…In addition, emerging literature has shown that some individuals with ADHD have a higher concurrence of immune-related comorbidities, such as asthma and atopic dermatitis (AD); thus, an immune-related cause for ADHD has been proposed. [22][23][24][25][26][27][28] At the same time, MF nonionizing radiation exposure has been reported to have an association with the immune system. 9,29-33 Thus, it is conceivable that in utero exposure to MF nonionizing radiation may specifically increase the risk of ADHD with an underlying immune cause.…”
Section: Outcome Measurement: Adhd Diagnosis and Immune-related Comormentioning
confidence: 97%
“…9,29-33 Thus, it is conceivable that in utero exposure to MF nonionizing radiation may specifically increase the risk of ADHD with an underlying immune cause. To examine this potential causal pathway, we divided children with ADHD into those with immune-related comorbidities (asthma or AD), as reported in the literature, [23][24][25][26][27] and those without these comorbidities. Both asthma and AD were identified based on physicians' diagnoses: ICD-9 codes of 493.x or ICD-10 codes of J45.x for asthma and ICD-9 codes of 691.8x or ICD-10 codes of L20.x for AD (excluding diaper or skin rash).…”
Section: Outcome Measurement: Adhd Diagnosis and Immune-related Comormentioning
confidence: 99%